Optical nonlinearities in semiconductor doped glass channel waveguides. - Banyai, William Charles. (The University of Arizona., 1988)
The nonlinear optical properties of a semiconductor-doped glass (SDG) channel waveguide were measured on a picosecond time-scale; namely, fluence-dependent changes in the absorption and the refractive index as well as the relaxation time of the nonlinearity. Slower, thermally-induced changes in the refractive index were also observed. The saturation of the changes in the absorption and the refractive index with increasing optical fluence is explained using a plasma model with bandfilling as the dominant mechanism. The fast relaxation time of the excited electron-hole plasma (20 ps) is explained using a surface-state recombination model. A figure of merit for a nonlinear directional coupler fabricated in a material with a saturable nonlinear refractive index is presented. The measured nonlinear change in the refractive index of the SDG saturates below the value required to effect fluence-dependent switching in a nonlinear directional coupler. Experiments with a channel-waveguide directional coupler support this prediction. However, absorption switching due to differential saturation of the absorption in the two arms of the directional coupler was observed.